Global Educational Data Mining Research Trends in Education: A Bibliometric Analysis and Implications for Transformational Leadership in Education - A’yun, Ummu Qurrota; Sulisworo, Dwi; Maryani, Ika (The Indonesian Institute of Science and Technology Research, 2025)
The education sector faces new challenges and opportunities in the digital era of big data and rapid technological advancement. This study aims to perform a comprehensive bibliometric analysis of global research trends in Educational Data Mining (EDM) from 2012 to 2024 and examine their implications for transformational leadership in education. We extracted relevant EDM publications from the Dimensions database using the PRISMA methodology and analyzed publication patterns, collaboration networks, and methodological trends. The analysis reveals a marked increase in EDM-focused research interest over time, accompanied by growing international and inter-institutional collaborations and evolving research approaches. Findings suggest that transformational educational leaders can leverage EDM insights, such as data-driven and predictive analytics, to enhance teaching effectiveness, encourage participative decision-making, and foster innovative learning environments. This bibliometric review provides critical insights for educators and policymakers on integrating EDM with transformational leadership practices and encourages further research on data-informed leadership in education.